Friends or foes? Economic growth and population health in contemporary Central America - Roberth Steven Gutiérrez Murillo (Social Medicine Publication Group, 2024)
This short communication poses some views about the provocative question "Does economic growth result in better population health?" which then leads us to reflect as public health practitioners in current times. Therefore, from this point of view, I will share some thoughts on the subject, especially bringing the case of Central American countries into this field. At first glance, this question seems easy to answer, yet several aspects must be investigated in as much detail as possible to draft a reasonable answer.